DAMPAK PENYALURAN DANA ZAKAT PADA PROGRAM OPERASI KATARAK DI YAYASAN DANA SOSIAL ALFALAH (YDSF) SURABAYA - Citra Nisaul Fadilah (Islamic Economic Law Programs, Faculty of Sharia and Law State Islamic University (UIN) of Sunan Ampel Surabaya., 2016)
The practice of zakat fund distribution by YDSF Surabaya have some impact, both positive and negative. The positive impact is that many disadvantaged communities who will get better health levels, also make harmony in the social environment, while its negative impact lies in the tendency of the poor who will ultimately depend mercy of others. When analyzed using the concept of zakat in the concept of Islamic law, where the beneficiaries of cataract surgery in Surabaya YDSF belonging to the class of the poor, then giving alms to them in accordance with the provisions of Islamic law, particularly its provisions on mustahik zakat. As to the form of zakat itself in the form of assistance for free cataract surgery is not a problem, because there is no obligation of zakat distribution should be a basic requirement only. As God has commanded in surah al-Baqarah ayah 195 to always try and not let ourselves fall into perdition.